Efektifitas Layanan Samsat Online Nasional Dalam Mewujudkan Pelayanan Yang Efektif Pada UPT Samsat Medan Selatan - Muhammad Fadli Harahap; Laylan Syafina (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
Salmonas is an abbreviation of National Online Samsat, a technologically advanced application that allows paying and approving annual vehicle taxes online. The aim of the national online service carried out by Samsat is a good step to provide simplicity in taxpayer activities for the taxpayers, namely the public. The aim of this research is to improve national online Samsat services so that the public can receive effective services at the South Medan Samsat UPT facilities. The method used in this research uses descriptive research combined with qualitative data analysis. Based on the results obtained, the Salmonas Service (National Online Samsat) at the South Medan Samsat is useful for building efficiency in community services at the Samsat office in South Medan, but some people may not yet know about the National Online Samsat because public awareness has not increased with the vehicle tax payment system by online.